2014
DOI: 10.1371/journal.pone.0090219
|View full text |Cite|
|
Sign up to set email alerts
|

R-Loops in Proliferating Cells but Not in the Brain: Implications for AOA2 and Other Autosomal Recessive Ataxias

Abstract: Disruption of the Setx gene, defective in ataxia oculomotor apraxia type 2 (AOA2) leads to the accumulation of DNA/RNA hybrids (R-loops), failure of meiotic recombination and infertility in mice. We report here the presence of R-loops in the testes from other autosomal recessive ataxia mouse models, which correlate with fertility in these disorders. R-loops were coincident in cells showing high basal levels of DNA double strand breaks and in those cells undergoing apoptosis. Depletion of Setx led to high basal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 56 publications
9
44
0
Order By: Relevance
“…Using this system, we observed that nuclear foci of this mutant and not wild‐type RNase H significantly accumulated in cells depleted of Ddx19 compared to control cells (Fig EV4D). R‐loops were observed throughout the nucleus, highly enriched in the nucleolar compartment, similar to the pattern previously observed in cells depleted of senataxin (Yeo et al , ), and consistent with the pattern of γH2AX staining and 53BP1 foci (Fig C). Of note, in cells depleted of Nxf1, R‐loops accumulated mainly close to the nuclear periphery (Fig A, upper panel), again consistent with the observed pattern of 53BP1 foci upon Nxf1 downregulation (Fig B and C), and in line with a function of Nxf1 at the nuclear face of the nuclear pore.…”
Section: Resultssupporting
confidence: 89%
“…Using this system, we observed that nuclear foci of this mutant and not wild‐type RNase H significantly accumulated in cells depleted of Ddx19 compared to control cells (Fig EV4D). R‐loops were observed throughout the nucleus, highly enriched in the nucleolar compartment, similar to the pattern previously observed in cells depleted of senataxin (Yeo et al , ), and consistent with the pattern of γH2AX staining and 53BP1 foci (Fig C). Of note, in cells depleted of Nxf1, R‐loops accumulated mainly close to the nuclear periphery (Fig A, upper panel), again consistent with the observed pattern of 53BP1 foci upon Nxf1 downregulation (Fig B and C), and in line with a function of Nxf1 at the nuclear face of the nuclear pore.…”
Section: Resultssupporting
confidence: 89%
“…In silico  analysis of the human genome identified a high number of RLFS (245 181) in 59% well-annotated genes (18). Consistent with these predictions, several recent genome-wide experimental studies mapped thousands of RNA:DNA hybridization signals distributed along human and mouse genomes and demonstrated that R-loops can be formed not only in the gene body but also in the upstream promoter regions (911) and transcription pause sites located downstream of the poly(A) signal (9,10,12,13,19). Formation of these R-loops in proximal promoter regions was shown to be involved in transcription initiation or elongation (9) and the recruitment of key pluripotency regulators (11).…”
Section: Introductionmentioning
confidence: 63%
“…However, a direct link between the regulation of R-loops and disease etiology is still missing. In fact mouse models that try to recapitulate the human disease show elevated R-loop formation, DNA damage and apoptosis in proliferating cells, but not in post-mitotic cells, like the brain neurons [43]. It is still possible that neurons are particularly sensitive to low levels of R-loop, or R-loop formation in other tissues indirectly impacts neuron function.…”
Section: R-loops In Human Diseasesmentioning
confidence: 99%